Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 238749 species occurrences available in GBIF matching the query: { "Country" : [ "is Ghana" ] } The dataset includes 238749 records from 333 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000580-150407101314760/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences